Computational Urban Planning and Management for Smart Cities. - (:unkn) unknown (Springer Nature, 2019)
The book contains a selection of the best articles presented at the CUPUM (Computational Urban Planning and Urban Management) conference, held in the second week of July 2019 at the University of Wuhan, China. The chapters included were selected based on a double-blind review process involving external reviewers.
Keywords: Stadtplanung; Stadtsystem; Smart City; Nachhaltige Entwicklung; Entwurfsmethode; Datenerfassung; Geodaten; Open Data; Informationstechnologie; Social Media; EDV-Einsatz; Simulation; Visualisierung; Datenanalyse; Mobilität; Stadtverkehr; Verkehrsverhalten